Image Protection by Intersecting Signatures - Chun-Hung Chen; Yuan-Liang Tang; Wen-Shyong Hsieh; Min-Shiang Hwang (Institute of Advanced Engineering and Science, 2014)
In this paper, we propose an exact image authentication scheme that can, in the best case, detect image tampering with the accuracy of one pixel. This method is based on constructing blocks in the image in such a manner that they intersect with one another in different directions. Such a technique is very useful to identify whether an individual image pixel has been tampered with.